Unraveling the nexus between fiscal policy uncertainty, environmental taxation, and life expectancy - Yongxian Fan; Muhammad Usman; Petra Poulova; Yong Wen (BMC Public Health)
Abstract Background The nexus between fiscal unpredictability and environmental responsibility is a narrative of paramount significance. Therefore, this study aims to explore the impact of fiscal policy uncertainty on life expectancy and the mediating role of environmental taxation on this relationship, particularly from the perspective of China. Empirical methodology To confirm such notions, statistical data is collected using the National Bureau of Statistics of China. The final dataset has yearly data from thirty Chinese provinces. The ordinary least squares technique to measure direct impact and the MED–SEM approach for mediating impact are used. Findings The regression estimates show a negative and statistically significant impact of fiscal policy uncertainty on life expectancy. Moreover, environmental taxation has a positive and statistically significant partial mediating effect on the direct relationship. Policy implications These results indicate that fiscal policy uncertainty can destabilize social security programs, housing support, and budgets, which consequently elevate poverty rates, adversely impact health, and possibly decline life expectancy. Moreover, when there is uncertainty in fiscal policy, governments can take advantage of this situation and introduce environmental taxes that provide the necessary funds to invest in the healthcare sector, encourage sustainable practices, and mitigate negative externalities. These results can significantly contribute to the public sector, environmental, and health economics fields and provide new research dimensions for academicians and policymakers.